Avaliação da via não formadora de imagem em pacientes com glaucoma: resposta pupilar à luz e distúrbios do sono - Gracitelli, Carolina Pelegrini Barbosa [UNIFESP] (2016)
This study was conducted to evaluate the non-forming image pathway in patients with glaucoma: analysis of pupillary reflex and sleep disturbance. This study was divided into five steps with the following purposes: 1. To assess the integrity of intrinsically photosensitive retinal ganglion cells (ipRGCs) using the pupillary light reflex (PLR). 2. To use polysomnography and the PLR to evaluate ipRGCs function. 3. To evaluate daytime sleepiness using the Epworth sleepiness scale (ESS) and to correlate the ESS score with ipRGCs function based on polysomnography and the PLR test. 4. Make a critical analysis of sleep disturbances in patients with glaucoma. 5. To examine the relationship between relative afferent pupillary defects and macular structural damage measured by macular thickness and macular ganglion cell-inner plexiform layer (mGCIPL) thickness in patients with glaucoma. Methods: This was a cross-sectional study. In the first moment, in order to design study numbers 1, 2, and 3, we included 76 eyes of 38 patients with primary open angle glaucoma and 36 eyes of 18 controls. For study numbers 1, 2, and 3, all patients had PLR using the Ganzfeld system. To preferentially stimulate ipRGCs, we used a 1 second 470 nanometers flash with a luminance of 250 cd/m2. Standard automated perimetry (SAP), and high-definition optical coherence tomography (OCT) were performed in all patients. In addition, polysomnography was performed and the ESS was administered to all patients. For study number 4, a literature review was performed about sleep disorders and ipRGCs function in glaucoma. For study number 5, we included 106 patients with primary open angle glaucoma and 85 controls. All subjects involved in study number 5 underwent standard automated perimetry and optic nerve and macular imaging using OCT. Pupil responses were assessed using an automated pupillometer which records the magnitude of relative afferent pupillary reflex. Results: 1. An association was observed between the average retinal nerve fiber layer (RNFL) thickness, as measured by OCT, and the sustained pupillary response to the blue flash (R2 = 0.403; p = 0,024). 2. The glaucoma patients had significantly lower average total sleep time, sleep efficiency and minimum oxyhemoglobin saturation, compared to the healthy subjects (p = 0.008, p = 0.002 and p = 0.028, respectively). Additionally, glaucoma patients had significantly higher arousal durations after falling asleep and more periodic limb movements (p = 0.002 and p = 0.045, respectively). There was an inverse correlation between rapid eye movement (REM) latency and peak of the pupillary response to the blue flash (p = 0.004). The total arousals were inversely correlated with the sustained blue flash response (p = 0.029). 3. The mean ESS score of the glaucoma patients was significantly higher than that of the control group (13.10 ± 5.14 and 9.10 ± 3.73, respectively, p = 0.029). Significant correlations were observed between the ESS score and the following polysomnographic parameters: sleep efficiency, arousal duration after falling asleep, arousals, and arousal index (p = 0.002, p < 0.001, p = 0.039, and p = 0.013, respectively). Regarding the PLR test, significant correlations were observed between the EES score and the peak and sustained responses to the blue flash with a luminance of 250 cd/m2. 4. According to previous studies, there was a correlation between glaucomatous disease and sleep disorders. 5. There was a fair correlation between RAPD score and asymmetric macular structural damage measured by intereye difference in mGCIPL thickness (R2 = 0.285, P < 0.001). The relationship between RAPD score and intereye difference in macular thickness was weaker (R2 = 0.167, P < 0.001). Intereye difference in RNFL thickness (R2 = 0.350, P < 0.001) and SAP mean deviation (R2 = 0.594, P < 0.001) had a stronger association with RAPD scores compared with the intereye difference in mGCIPL and macular thickness. Conclusion: 1. This study showed a correlation between the mean RNFL thickness and the pupillary light response. 2. This study demonstrated that decreased ipRGCs function caused by glaucoma affected not only the pupillary response but also the sleep quality. 3. Decreased ipRGCs function caused by glaucoma is associated with exacerbated sleep disorders, as assessed by the ESS and polysomnography, and impaired PLR. 4. With previous studies and with our results there is strong evidence that glaucoma leads to RGC death, including ipRGCs death and this can affect not only the image-forming but also the non-image-forming visual systems. 5. Objective assessment of pupillary responses using a pupillometer was associated with asymmetric macular structural damage in patients with glaucoma.